Between Past and Future - 2/3
Recording of the first conference panel entitled "1989 and its Aftermath through the Eyes of the Media” part of the “Between Past and Future” international conference organized by CEU and the University of Maryland and hosted by CEU in March 1999. The participants were American and Hungarian print, television and radio journalist who covered the events in 1989. The panel is chaired by Kati Marton (Author and Journalist). The members of the panel are R. W. Apple Jr. (Chief Correspondent, “New York Times”), Barrie Dunsmore (Former Senior Correspondent, ABC News), James Carney (Political Correspondent, “Time Magazine”), Flora Lewis (Senior Columnist, “New York Times” Syndicate), Ambassador Richard Holbrooke (U.S. Special Envoy to Yugoslavia) and György Bolgár (Journalist and Broadcaster, Hungarian Radio). The discussion between the members of the panel is followed by a debate between the journalists and the audience, including conference participants Ambassador Peter Tufo, Prof. Tamás Gáspár Miklós, political writer Timothy Garton Ash and Prof. István Rév.